Implementasi Sistem Informasi KRS Online dengan Metode Software Development Life Cycle Model Waterfall - Sanjaya Pinem; Viktor Edison Hutagaol; Victor Maruli Pakpahan (Teknik Informatika Universitas Pamulang, 2021)
Efarina University is one of the universities in North Sumatra that still uses KRS manually. Using Course Selection manually will cause the data not well organized. It will increase the risk of damage and loss of data for active students and alumni, especially now that we have entered the era of the industrial revolution 4.0. Therefore, an integrated information system is needed to manage and manage student Course Selection data properly. For that, a method is needed to implement all the processes for creating the application. The method used is the Software Development Life Cycle (SDLC) Waterfall model with five (5) fundamental stages, 1) requirements analysis, 2) system design using UML (Unified Modeling Language), 3) implementation of the planned system, 4) evaluation with blackbox testing to ensure the system runs well, and lastly 5) repair (maintenance). With this method, the application runs in line with the previous plan and thus and reduces data loss for course selection. It is also easier for lecturers and students to fill out and implement student course selection administration.